In vitro cytotoxicity evaluation and phytochemical analysis of Ajuga reptans L. extracts - Çaşkurlu, Ayşegül; Karavuş, Şule Nur; Biltekin, Sevde Nur; Helvacı, Esra Zeynep; Karadağ, Ayşe Esra (Marmara University, 2023)
The aim of this study was to evaluate phytochemical composition of Ajuga reptans L. (Lamiaceae) aerial parts (separately flower and leaf) methanol, aqueous-methanolic extracts, and their cytotoxic activities. The phytochemical analysis was performed high-performance liquid chromatography (HPLC). Caffeic acid, p-coumaric, gallic, chlorogenic, ferulic acids, kaempferol, rutin, quercetin, quercetin-3-O-galactoside, and quercitrin were used as reference substances by HPLC in all samples. The major compounds in the extract were found as ferulic acid, caffeic acid, rutin, and quercetin-3-O-galactoside. Cytotoxicity was investigated using methyl thiazole tetrazolium (MTT) assay. Cytotoxic evaluation of the extracts against cancer (MCF7, PC3, and A549) and healthy human embryonic kidney cell line (HEK293) cell lines by MTT. Compared to other cells, the methanol extract of A. reptans demonstrated high selectivity against PC3 cells (IC50: 95 ± 0.99 µg/mL) and selectivity index was four times higher than reference drug colchicine. (IC50: 95 ± 0.99 µg/mL, SI: 6.10). A. reptans demonstrated antiproliferative potential against prostate and lung cancer cells. Therefore, additional investigations are needed to study the mechanism of the cytotoxicity for A. reptans.
Keywords: Ajuga; Cytotoxicity; HPLC; Lamiaceae